The Eastern Question and its impact on Russian politics (Journal of the College of Basic Education, 2022)
The Eastern Question (1812-1830) is a term applied to the problems that occurred in southeastern Europe as a result of the deterioration of the authority of the Ottoman Empire and the competition that occurred after it between the competing powers (). Rather, it is an issue of the existing dispute between some European countries and the Ottoman Empire regarding the countries under its authority, in other words, it is the issue of the presence of the Ottoman Empire itself in Europe (). And this conflict, which continued as a conflict between Christianity and Islam, i.e. a matter of intermittent crusade wars between the states established by the command of Islam and the Christian states, and this is an interpretation that is not entirely correct, because the states whose existence the Ottoman state disputed are not hostile to them in the name of religion only, but in most cases they are hostile to them out of greed. In obtaining something from its property, and history has shown us many cases in which religion was used only as a weapon and as a cover.